Pengaruh Supervisi Akademik Pengawas, Kepemimpinan Kepala Sekolah dan Disiplin Kerja terhadap Kinerja Guru - Ibnu Jarir; Sri Haryati; Rhini Fatmasari (Mahesa Research Center, 2022)
The objective of this study was to examine the influence of supervisor's academic supervision, principal's leadership and work discipline on teacher performance at the Bulu District Elementary School. This study uses quantitative research methods. The population of this study were 293 teachers from 25 schools. The number of samples taken in the study were 158 teachers. The research instrument used was a questionnaire. The data analysis method used is single regression and multiple regression. Based on the results of the analysis, it can be seen that (1) academic supervision of supervisors has a positive and significant effect on the performance of Bulu District Elementary School teachers (2) Principal leadership has a positive and significant effect on the performance of Bulu Subdistrict Elementary School teachers (3) Work discipline has a positive and significant effect on performance of district elementary school teachers (4) Academic supervision of supervisors, Principal leadership and work discipline have a simultaneous effect on the performance of teachers in Bulu District Elementary School.